Current Trends in Antibiotic Resistance of Gram-Negative Pathogens of Nosocomial Infections in the Rostov Region - O. Yu. Kutsevalova; O. I. Kit; N. I. Panova; D. A. Rozenko; S. V. Yakubenko; Yu. A. Gevorkyan; D. A. Kharagezov; D. V. Martynov; V. N. Malygin; A. Yu. Khindikaynen; G. V. Yankovskaya; O. A. Yegorova; et al. (Антибиотики и Химиотерапия, 2020)
Every year the problem of resistance of bacterial pathogens of infections in various localizations is becoming increasingly important for doctors of different specialties. This is especially true for clinicians working in the intensive care unit (ICU). Every day we have to deal with the problem of treating infections, primarily related to the provision of medical care (HAI), in patients with severe comorbidities, when timely diagnosis and adequate empirical antibiotic therapy play a key role in saving the patient's life. The list of «problematic» pathogens is constantly expanding. In addition to «traditional» pathogens of nosocomial infections well known to physicians such as Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus, the importance of other resistant microorganisms of the Enterobacteriaceae family (producers of ^-lactamase extended spectrum - ESBL), non-fermenting bacteria (Acinetobacter spp., in particular), as well as microscopic fungi has increased.